Experiences of menstrual restrictions: Freedom lost and never regained - Arijita Dutta; Aishika Chakraborty; Olivia Sarkar (International Journal of Educational Research Open, 2024)
Among numerous issues that make experiences during menstruation an impediment to gender equity, restrictions on daily activities is a concern about limiting individual freedom. Studies of menstrual restrictions have identified the arrays of “dos-and-don'ts”, but what remained missing was a detailed exploration into its origin, nature, correlates and the reasons behind their uncanny consistency over time. This paper, using primary survey of 1200 married young adults in two eastern states in India, adds to the existing literature by identifying the nature of restrictions, the changes in its contour with marriage and their internalization. Classifying restrictions in three broad categories, (restrictions on self, restrictions over household activities and restrictions over worship), the paper finds that nearly all woman are barred from performing rituals. While marriage increases the restrictions on women's agency to eat, go out, sleep in usual home or have sexual activities, it reduces the restrictions on household chores (cooking, serving). Strikingly, restrictions on herself do not alter with education or menstrual literacy. However, fitting logistic regression models over subsamples of hygienic menstrual product-users, finds restrictions are higher for backward classes and those who incorrectly define menstruation. Astonishingly, women do not find menstrual restrictions to be subduing and is reluctant in aspiring for changing community's perception, letting this thrive through generations. They only aspire for better menstrual products. This study shows that a holistic policy should target ‘changing perceptions’ rather than ‘changing protections’, to usher in a menstrual experience with freedom. Educating girls and their elderly care-givers (mothers, grandmothers or mothers-in-law) about this physiological process, giving them a space to discuss and fight the concept of impurity of their bodies can actually gift them a better living experience for sure.